Nano borate bioactive glass as well as preparation method and application thereof
The preparation of nanoborate bioactive glass by microemulsion-assisted sol-gel method solves the problems of complex preparation process, large energy consumption and poor size controllability in the prior art, and achieves efficient preparation of nano size and good biological activity.
Patent Information
- Application Number
- CN202411892911.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-20
- Publication Date
- 2025-03-21
AI Technical Summary
The existing borate bioactive glass preparation process is complex, the energy consumption is large, and the synthesis efficiency is low. The glass products are easy to agglomerate and have poor controllability, making it difficult to achieve nano-size preparation with good dispersion.
Using a microemulsion-assisted sol-gel method, a stable microemulsion system was formed by adding surfactant to the aqueous ethyl acetate dispersion, and a boron source, a calcium source and a phosphorus source were added for reaction, followed by calcination to prepare nanoborate bioactive glass.
The prepared nanoborate bioactive glass particles have a large specific surface area, uniform size, and nano-scale particle size, which has good dispersion and biological activity. The process conditions are mild and controllable, and the energy consumption is low, which improves the preparation efficiency and performance stability.
Smart Images

Figure CN119661075A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of biomedical material preparation, and specifically relates to a nano borate bioactive glass and a preparation method and application thereof. Background Art
[0002] Bioactive Glasses (BG) is a type of material that can repair, replace and regenerate the body and form bonds between tissues and materials. 2 , P 2 O 5 、Na 2 Silicate glass, which is composed of components such as O and CaO, can degrade in the body at a rate that matches bone formation. The degradation products have the function of regulating cell proliferation and differentiation and promoting the expression of osteogenesis-related genes. It is widely used in the field of tissue repair and regenerative medicine.
[0003] Silicate bioactive glass (SBG) can simultaneously introduce multiple elements necessary for human metabolism, such as boron, due to its unique network structure. As one of the trace elements in the human body, boron can not only promote the combination of calcium with bones, joints and cartilage, but also, as part of bone metabolism, synergize with vitamin D, calcium and magnesium to play anti-inflammatory and antioxidant functions. Generally, boron can form borosilicate or borate bioactive glass by partially or completely replacing the silicon-oxygen network. Due to the difference between the trivalent electron structure of boron and the tetravalent structure of silicon, borate glass and traditional silicon-based glass have great differences in structure, thermodynamic properties and biological behavior in vitro and in vivo, which has aroused widespread research interest. Borate bioactive glass (BBG) is generally prepared by melting method, that is, mixing boron-containing compounds with calcium, phosphorus and other compounds in a certain proportion, and then heating them to 1200℃~1500℃ in a precious metal or ceramic crucible to melt, and inhibiting crystallization by quenching to obtain amorphous glass. This method is not only costly and energy-intensive, but also dangerous. The presence of volatile components during the melting process and the uneven distribution of the components make it challenging to control the glass composition. In addition, the glass prepared by the melting method is generally in block form and needs to be ground and sieved at high energy before further use. The particles obtained by grinding are mostly micrometer-sized, with large differences in particle size and low biological activity, which limits its research and application in the field of nanomedicine.
[0004] In recent years, people have also explored the use of sol-gel technology to prepare nano-borate bioactive glass. The sol-gel method uses liquid precursors to gel the glass network through hydrolysis and condensation reactions. Subsequently, the gel is dried and calcined to densify the amorphous glass and remove any organic products. However, the low network connectivity of borate glass makes it difficult to gel. So far, only a few studies have reported the sol-gel processing of borate bioactive glass, and there are generally problems such as low synthesis efficiency, easy agglomeration of particles, and poor controllability of particle size, which is not conducive to subsequent applications in the biomedical field. Summary of the invention
[0005] In order to overcome the shortcomings of the above-mentioned prior art, the purpose of the present invention is to provide a nano-borate bioactive glass and a preparation method and application thereof, so as to solve the technical problems that the existing borate bioactive glass preparation process is complex, energy consumption is high, synthesis efficiency is low, the glass product is easy to agglomerate, size controllability is poor, and it is difficult to achieve nano-size preparation with good dispersion.
[0006] In order to achieve the above object, the present invention adopts the following technical solutions: In order to achieve the above-mentioned object of the invention, in a first aspect, the present invention provides a method for preparing a monodisperse nano-borate bioactive glass, comprising the following steps: 1) At a certain temperature, a surfactant is added to an aqueous dispersion of ethyl acetate to form a stable microemulsion system, and the pH value is adjusted to alkaline to obtain an alkaline microemulsion system; 2) adding a boron source, a calcium source and a phosphorus source for forming borate bioactive glass to the alkaline microemulsion in sequence to react and obtain a precursor solution; 3) After the precursor solution has reacted and precipitated, the precipitate is collected, and the precipitate is washed and dried; 4) calcining the dried and collected precipitate to obtain nano-borate bioactive glass.
[0007] Preferably, in step 1), the volume ratio of ethyl acetate to water in the aqueous dispersion of ethyl acetate is 1:(1-4); Further preferably, ethyl acetate is used as the oil phase of the reaction solvent in order to form an oil-in-water microemulsion reaction system with water, and the volume ratio of ethyl acetate to water in the aqueous dispersion of ethyl acetate is 1:(1.5-3).
[0008] Preferably, organic solvents such as cyclohexane that can form a good microemulsion system with water can be used as the oil phase of the reaction, but different oil-in-water systems involve different reaction conditions such as the oil-water ratio.
[0009] Preferably, in step 1), a base is used to adjust the pH value to alkaline; the pH value range is 7.5 to 10.5; Further preferably, the pH value ranges from 7.5 to 9.5; More preferably, the base includes at least one of an inorganic base and an organic base.
[0010] More preferably, the inorganic base is ammonia water, sodium hydroxide or potassium hydroxide, etc.; the organic base is triethanolamine, trimethylamine or triethylamine, etc. Theoretically, as long as the pH value is within the appropriate range, it is irrelevant to the type of alkaline reagent selected. However, it is necessary to further consider not to introduce other impurity ions when using it.
[0011] Preferably, in step 1), the surfactant includes at least one of cationic surfactants such as dodecylamine, polyethylene glycol or dodecyltrimethylammonium.
[0012] Preferably, in step 2), the boron source includes tributyl borate; the phosphorus source includes triethyl phosphate; and the calcium source includes calcium nitrate.
[0013] Preferably, the mass ratio of the boron source, phosphorus source, calcium source and surfactant is (20-90): (1-15): (10-65): (3-25); Further preferably, the mass ratio of the boron source, phosphorus source, calcium source and surfactant is (30-80): (2-10): (20-60): (5-20).
[0014] Preferably, in step 1), the certain temperature range is 20-80°C; More preferably, the certain temperature range is 30-60°C.
[0015] Preferably, in step 4), the calcination temperature is 400-800°C; the sintering system during the calcination process is: starting from room temperature, the temperature is increased at a heating rate of 3-15°C / min; More preferably, the calcination temperature is 500-700°C.
[0016] More preferably, the calcination treatment is performed at a heating rate of 5-10° C. / min.
[0017] In a second aspect, the present invention provides a monodisperse nano borate bioactive glass. The borate bioactive glass has a chemical composition of aXO·bB 2 O 3 ·cP 2 O 5, wherein a, b and c are molar fractions, a is 3-50, b is 40-96, c is 1-10, and X is Ca; one or more of Mg and Sr may also be considered.
[0018] The chemical composition of the nano borosilicate bioactive glass is 3CaO·96B 2 O 3 1P 2 O 5 、12CaO·85B 2 O 3 ·3P 2 O 5 、25CaO·70B 2 O 3 ·5P 2 O 5 、30CaO·66B 2 O 3 ·4P 2 O 5 、42CaO·54B 2 O 3 8P 2 O 5 or 54CaO·42B 2 O 3 ·4P 2 O 5 .
[0019] Preferably, the particle size of the nano-borosilicate bioactive glass is 20-800 nm.
[0020] Further preferably, the particle size of the nano-borosilicate bioactive glass is 100-500 nm.
[0021] In a third aspect, the present invention also discloses the use of the above-mentioned nano-borate bioactive glass in the preparation of biomedical materials.
[0022] Preferably, the biomedical materials include materials that promote tissue repair and regeneration.
[0023] Compared with the prior art, the present invention has the following beneficial effects: The present invention selects ethyl acetate as the oil phase of the reaction solvent, the purpose is to form an oil-in-water microemulsion reaction system with water, and adopts a microemulsion-assisted sol-gel method to prepare borate bioactive glass, so that the prepared borate bioactive glass particles have a large specific surface area, uniform and controllable size, a regular spherical shape, good dispersibility, and a particle size of nanometers, so the reaction activity is high, the biological activity is high, and the degradation rate in vivo and in vitro is fast, and it can be directly used without subsequent grinding and processing. The surface of the monodisperse borate bioactive glass is rich in a large number of active hydroxyls, which provides an anchor point for the subsequent modification and application of the bioactive glass. In addition, the present invention does not require high temperature, and the process conditions are mild and controllable, which can effectively ensure the stable performance of the prepared monodisperse borate bioactive glass, and effectively improve the preparation efficiency, reduce the cost, and overcome the existing high-temperature melting method. The preparation of nano borate bioactive glass cannot be achieved, and the existing sol-gel method for preparing borate bioactive glass has low synthesis efficiency and safety, poor particle dispersibility and poor size controllability, and it is difficult to obtain glass for nanoscale research and application.
[0024] Furthermore, the reason for adjusting the pH value to alkaline is that tributyl borate will quickly hydrolyze to form boric acid and butanol under acidic or even neutral conditions, and if the hydrolysis rate is too fast, it will not be able to participate in the reaction at a speed that matches the formation of bioactive glass, resulting in a large amount of boron source lost during the reaction. The alkaline / weakly alkaline emulsion system will inhibit the hydrolysis of tributyl borate to a certain extent, so that the boron source can be retained in the oil phase after addition. When the calcium source is added, the calcium ions will continuously consume the boric acid formed by the hydrolysis of tributyl borate, and further promote the hydrolysis reaction of tributyl borate to move forward, and continuously combine with calcium ions to form a bioactive glass precursor, and the boron source can also undergo a hydrolysis reaction at a speed that matches the bioactive glass. BRIEF DESCRIPTION OF THE DRAWINGS
[0025] Figure 1 The figure is a schematic diagram of the process flow of the method for preparing the nano-borate bioactive glass of the present invention; Figure 2 This is a scanning electron microscope image of the nano-borate bioactive glass of Example 1 of the present invention; wherein the left image is a SEM image magnified 20,000 times, and the right image is a SEM image magnified 100,000 times; Figure 3 This is a scanning electron microscope image of the nano-borate bioactive glass of Example 2 of the present invention; wherein the left image is a SEM image magnified 20,000 times, and the right image is a SEM image magnified 100,000 times; Figure 4 This is a scanning electron microscope image of the nano-borate bioactive glass of Example 3 of the present invention; wherein the left image is a SEM image magnified 20,000 times, and the right image is a SEM image magnified 100,000 times; Figure 5 The transmission electron microscope image and mapping image of the nano-borate bioactive glass of Example 3 of the present invention; Figure 6 This is a scanning electron microscope image of the borate bioactive glass prepared by the melting method in Comparative Example 1 of the present invention; wherein the left image is a SEM image magnified 20,000 times, and the right image is a SEM image magnified 100,000 times; Figure 7 This is a scanning electron microscope image of the borate bioactive glass prepared by the sol-gel method in Comparative Example 2 of the present invention; wherein the left image is a SEM image magnified 20,000 times, and the right image is a SEM image magnified 100,000 times. DETAILED DESCRIPTION
[0026] In order to enable those skilled in the art to better understand the scheme of the present invention, the technical scheme in the embodiments of the present invention will be clearly and completely described below in conjunction with the drawings in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work should fall within the scope of protection of the present invention.
[0027] It should be noted that the terms "including" and "having" and any variations thereof in the specification and claims of the present invention and the above-mentioned drawings are intended to cover non-exclusive inclusions. For example, a process, method, system, product or apparatus comprising a series of steps or units is not necessarily limited to those steps or units clearly listed, but may include other steps or units that are not clearly listed or inherent to these processes, methods, products or apparatus.
[0028] The mass of each component mentioned in the description of the embodiments of the present invention may not only refer to the specific content of each component, but also indicate the proportional relationship between the masses of the components. Therefore, as long as the content of each component is proportionally enlarged or reduced according to the description of the embodiments of the present invention, it is within the scope disclosed in the description of the embodiments of the present invention. Specifically, the mass described in the description of the embodiments of the present invention may be a mass unit known in the chemical industry such as μg, mg, g, kg, etc.
[0029] The present invention is further described in detail below in conjunction with the accompanying drawings: The present invention provides a method for preparing nano borate bioactive glass. The preparation process of the nano borate bioactive glass is as follows: Figure 1 As shown, it includes the following steps: S01: adding a surfactant to an aqueous dispersion of ethyl acetate to form a stable microemulsion system; S02: adding a boron source, a calcium source and a phosphorus source for forming borate bioactive glass to the microemulsion in sequence at a certain temperature and stirring the microemulsion sufficiently to obtain a precursor solution; S03: After the precursor solution is reacted and precipitated, the precipitate is collected, and the precipitate is washed and dried; S04: calcining the collected and dried precipitate.
[0030] Specifically, in step S01, ethyl acetate is dispersed in an aqueous solution to form an oil-in-water microemulsion to induce the shape and size of the particles. The template has a structural guiding effect on the one hand, and is used to maintain the stability of the microemulsion droplets on the other hand.
[0031] Furthermore, the template agent is selected as a surfactant such as CTAB (hexadecyltrimethylammonium bromide). On the one hand, CTAB can stabilize the oil-water interface and maintain the stability of the microemulsion, so that the microemulsion droplets are stable spherical, making the subsequently prepared nanoparticles more regular in morphology and more uniform in size; on the other hand, the removal of CTAB in the subsequent calcination process is expected to improve the pore structure of the nanoparticles.
[0032] Preferably, in a specific embodiment, the stable microemulsion system in step S01 is preferably prepared according to the following method: S011: Add a certain amount of deionized water to a beaker and preheat it to a specified temperature in a water bath; S012: adding a certain amount of ethyl acetate to the preheated deionized water, and mixing to obtain a first mixed system; S013: adding a surfactant to the first mixed system, and adding an alkali to adjust the pH value to obtain a second mixed system, i.e., the stable microemulsion system; Wherein, in step S011, the temperature range is 20°C to 60°C.
[0033] In step S012, during the mixing process to obtain the first mixed system, ethyl acetate and water should be fully mixed, and the mixing process can be accelerated by means of magnetic stirring or the like; the volume ratio of ethyl acetate to water is 1:(1-4), preferably 1:(1.5-3).
[0034] In step S013, the surfactant should be fully dissolved during the addition of the surfactant, such as by means of magnetic stirring, heating, etc. to accelerate the dissolution of the surfactant; the surfactant may include at least one of cationic surfactants such as dodecylamine, polyethylene glycol, or dodecyltrimethylammonium, with a mass fraction ranging from 5% to 20%. The base is added to adjust the pH value, and the base includes inorganic bases such as ammonia water and organic bases such as triethanolamine; the pH value range is further preferably 7.8 to 9.6.
[0035] Specifically, in step S02, the precursor solution is preferably prepared according to the following method: S021: adding the boron source into the second mixed system for mixing to obtain a third mixed system; S022: adding the phosphorus source into the third mixed system for mixing to obtain a fourth mixed system; S023: adding the calcium source into the fourth mixed system for mixing to obtain the precursor solution; In step S021, the boron source is preferably added to the second mixed system in multiple batches, that is, slowly added, preferably stirred and heated during the addition process, preferably heated in a water bath, and stirred for more than 30 minutes after the addition is completed. In one embodiment, the boron source is preferably tributyl borate.
[0036] In step S022, the phosphorus source is preferably added to the third mixed system in multiple batches, that is, slowly added, preferably stirred and heated during the addition process, preferably heated in a water bath, and stirred for more than 30 minutes after the addition is completed. In one embodiment, the phosphorus source is preferably triethyl phosphate.
[0037] In step S023, the calcium source is preferably added to the fourth mixing system in multiple batches, that is, slowly added, preferably stirred and heated during the addition process, preferably heated in a water bath, and stirred for more than 30 minutes after the addition is completed. In one embodiment, the calcium source is preferably calcium nitrate.
[0038] The reason for considering adding in batches is that adding at the same time will cause serious agglomeration of the nanoparticles, affecting the performance of the product.
[0039] The amounts of boron source, phosphorus source and calcium source added to form borate bioactive glass can be added according to the proportion of borate bioactive glass. For example, in one embodiment, the molar ratio of the boron source, phosphorus source and calcium source is controlled to be (30-80): (2-10): (20-60).
[0040] Therefore, by controlling and optimizing the preparation method of the mixed system in the above step S02 and further controlling and optimizing the dosage ratio of each component, a stable sol-gel system can be effectively prepared, thereby further increasing the specific surface area of the borate bioactive glass particles, improving their size uniformity, making their particle size nanometer-scale, and improving their biological activity.
[0041] In step S03, after the precursor solution has fully undergone precipitation reaction, solid-liquid separation is performed on it, and the precipitate is collected, such as centrifugal separation. The precipitate is washed to remove impurities attached to the precipitate, such as residual solvent and reactants that have not undergone precipitation reaction. In one embodiment, the precipitate can be washed with water or alcohol. In a specific embodiment, after washing with deionized water and ethanol alternately for 3 times, the obtained white precipitate is placed in a vacuum drying oven and dried for 12 hours.
[0042] In the step S04, after the precipitate is calcined, nano-borate bioactive glass is generated, wherein the components such as the template are removed.
[0043] In one embodiment, the calcination temperature is 400-800°C, preferably 500-700°C, and more preferably 500°C. The calcination time should be sufficient, such as 2-4 hours, preferably 3 hours. The calcination temperature rise rate range includes 5-10°C / min. Preferably, in one embodiment, the temperature is raised to the calcination temperature at a rate of 10°C / min. The calcination temperature can effectively ensure the formation of nano-borate bioactive glass and the removal of impurities, and improve the regularity of the nanoparticles and the uniformity of their size.
[0044] As described above, the preparation method of the nano borate bioactive glass adopts a microemulsion-assisted sol-gel method, so that the prepared borate bioactive glass particles have a large specific surface area, uniform size, nanometer particle size, safety and high biological activity. In addition, the preparation method has mild and easy-to-control process conditions and low energy consumption, which can effectively ensure the stable performance of the prepared borate bioactive glass, and can be directly used without post-processing such as grinding, thereby effectively improving the preparation efficiency and reducing the production cost.
[0045] In addition, since the preparation method of the nano borate bioactive glass can give the prepared borate bioactive glass the characteristics of large specific surface area, uniform size, nano-scale particle size, safety and high bioactivity, it can be further used as a raw material for various forms of bioactive glass materials such as films, coatings, fibers and scaffolds. In addition, the nano borate bioactive glass with an extremely small size of 100-300nm can be internalized by cells, can directly release bioactive ions such as boron, calcium and phosphorus in cells to stimulate and induce cells, and can regulate cell proliferation, differentiation and gene expression at the nanoscale, and has broad research and application value.
[0046] The following is an illustration of the method for preparing the nano-borate bioactive glass according to the embodiment of the present invention through a plurality of specific embodiments and comparative examples.
[0047] Example 1 This embodiment provides a method for preparing nano-borate bioactive glass, and the preparation method comprises the following steps: 1) Accurately measure 80 mL of water with a measuring cylinder, preheat in a 40 ℃ water bath for 5 min, then accurately weigh 1.4 g of hexadecyltrimethylammonium bromide, slowly add it into the water under magnetic stirring, stir for 15 min, and wait until the solution becomes clear and transparent to obtain a mixed solution; 2) Accurately weigh 40 mL of ethyl acetate and add it to the above mixed solution, stirring for 30 min; 3) After a stable microemulsion is formed, accurately measure 8.87 mL of tributyl borate and slowly add it to the reaction system in step 2) and continue stirring for 30 min; 4) Accurately measure 0.17 mL of triethyl phosphate and slowly add it dropwise to the reaction system in step 3). Continue stirring for 30 minutes after the addition is complete; 5) Accurately weigh 1.42 g of calcium nitrate tetrahydrate and add it to the reaction system in step 4). After the calcium nitrate tetrahydrate is completely dissolved, continue stirring for 3 hours; 6) Centrifuge the reaction system in step 5) and discard the supernatant to obtain a white precipitate. Wash the precipitate with deionized water and ethanol alternately for 3 times, and then place the obtained white precipitate in a vacuum drying oven and dry it for 12 hours. 7) The dried white precipitate is placed in a muffle furnace, and the temperature is raised from room temperature to 500°C (10°C / min), and heat treated for 3 hours, and then cooled naturally to obtain a white powder, i.e., nano-scale borate bioactive glass. The molar ratio of each component in the bioactive glass prepared in this example is: 66B 2 O 3 , 30CaO and 4P 2 O 5 .
[0048] The white powder obtained in Example 1, that is, the nano-borate bioactive glass, was sprayed with gold and observed under a scanning electron microscope (SEM). The results are as follows: Figure 2 As shown, the synthesized borate bioactive glass is spherical particles with uniform particle size distribution and a diameter between 100-300 nm.
[0049] Example 2 This embodiment provides a method for preparing nano-borate bioactive glass, and the preparation method comprises the following steps: 1) Accurately measure 80 mL of water with a measuring cylinder, preheat in a 40 ℃ water bath for 5 min, then accurately weigh 1.4 g of hexadecyltrimethylammonium bromide, slowly add it into the water under magnetic stirring, and stir for 15 min until the solution becomes clear and transparent to obtain a mixed solution; 2) Accurately weigh 40 mL of ethyl acetate and add it to the above mixed solution, stirring for 30 min; 3) After a stable microemulsion is formed, accurately measure 7.26 mL of tributyl borate and slowly add it to the microemulsion, and continue stirring for 30 minutes; 4) Accurately measure 0.17 mL of triethyl phosphate and slowly add it dropwise to the reaction system in step 3). Continue stirring for 30 minutes after the addition is complete; 5) Accurately weigh 2.48 g of calcium nitrate tetrahydrate and add it to the reaction system in step 4). After the calcium nitrate tetrahydrate is completely dissolved, continue stirring for 3 hours; 6) The reaction system obtained in step 5) was centrifuged, and a white precipitate was obtained after discarding the supernatant. After washing with deionized water and ethanol alternately for 3 times, the obtained white precipitate was placed in a vacuum drying oven and dried for 12 hours; 7) The dried white precipitate is placed in a muffle furnace, and the temperature is raised from room temperature to 500°C (10°C / min), and heat treated for 3 hours, and then cooled naturally to obtain a white powder, i.e., nano-scale borate bioactive glass. The molar ratio of each component in the bioactive glass prepared in this example is: 54B 2 O 3 , 42CaO and 4P 2 O 5 . The white powder obtained in this example, namely the nano borate bioactive glass, was sprayed with gold and then observed under a scanning electron microscope (SEM). Figure 3 As shown, the synthesized borate bioactive glass is spherical particles with uniform particle size distribution and a diameter between 100-300 nm.
[0050] Example 3 This embodiment provides a method for preparing nano-borate bioactive glass, and the preparation method comprises the following steps: 1) Accurately measure 80 mL of water with a measuring cylinder, preheat in a 40 ℃ water bath for 5 min, then accurately weigh 1.4 g of hexadecyltrimethylammonium bromide, slowly add it into the water under magnetic stirring, and stir for 15 min until the solution becomes clear and transparent to obtain a mixed solution; 2) Accurately measure 40 mL of ethyl acetate and add it to the above mixed solution, stirring for 30 minutes; 3) After a stable microemulsion is formed, accurately measure 5.65 mL of tributyl borate and slowly add it to the microemulsion, and continue stirring for 30 minutes; 4) Accurately measure 0.17 mL of triethyl phosphate and slowly add it dropwise to the reaction system in step 3). Continue stirring for 30 minutes after the addition is complete; 5) Accurately weigh 3.19 g of calcium nitrate tetrahydrate and add it to the reaction system in step 4). After the calcium nitrate tetrahydrate is completely dissolved, continue stirring for 3 hours; 6) After stirring for 3 hours, the reaction system was centrifuged and the supernatant was discarded to obtain a white precipitate. After washing with deionized water and ethanol alternately for 3 times, the obtained white precipitate was placed in a vacuum drying oven and dried for 12 hours; 7) Place the dried white precipitate in a muffle furnace, raise the temperature from room temperature to 500°C (10°C / min), heat treat for 3 hours, and then cool naturally to obtain a white powder, which is nano-scale borate bioactive glass. The molar ratio of each component in the bioactive glass obtained in this example is: 42B 2 O 3 , 54CaO and 4P 2 O 5 . The white powder obtained in this example, namely the nano borate bioactive glass, was sprayed with gold and then observed under a scanning electron microscope (SEM). Figure 4 As shown, the synthesized borate bioactive glass is spherical particles with uniform particle size distribution and a particle diameter between 100-300 nm.
[0051] In order to better demonstrate the microscopic morphology and element distribution of the nano-borate bioactive glass, a transmission electron microscope (TEM) was used to measure the sample. The sample TEM image, high-angle annular dark field image (HAADF) and EDX energy spectrum element composition and distribution image are shown in the figure. Figure 5 As shown, it can be clearly observed that the prepared nano-borate bioactive glass presents a uniform spherical shape with a uniform particle size distribution, a particle diameter of 100~300 nm, and the boron, calcium and phosphorus elements are evenly distributed, which deeply reflects the advantages of the nano-borate bioactive glass preparation method.
[0052] Comparative Example 1: This comparative example prepares a borate bioactive glass (BBG), and the difference between this comparative example and the embodiment is that a melting method is used. In short, the required raw materials such as boron source, calcium source and phosphorus source are uniformly mixed and melted at 1200°C, and then quenched to form a glass block, which is crushed, ground and sieved through a stainless steel mesh to obtain BBG particles (white powder) with a diameter of 40µm or less.
[0053] The white powder prepared in this comparative example 1 was subjected to gold spraying and observed under SEM. The results are as follows: Figure 6 As shown, the borate bioactive glass synthesized by the melting method has irregular shapes, poor particle dispersion and size uniformity, and the particle size can only reach the micron level, making it difficult to use for nanoscale research and applications.
[0054] Comparative Example 2: This comparative example prepares a borate bioactive glass (BBG). The difference between this comparative example and the embodiment is that the sol-gel method reported in the literature is used. In short, the required boron source, calcium source and phosphorus source and other raw materials are sequentially added to a solution of nitric acid, water and anhydrous ethanol, stirred and mixed to obtain a transparent solution, and the transparent solution is aged in a sealed bottle for 1 day and then heated to evaporate the solvent to obtain a transparent gel, and the white precipitate is collected after drying, calcined at high temperature, and then ground and sieved to a particle size of less than 40μm to obtain the borate bioactive glass.
[0055] The white powder prepared in this comparative example 2 was subjected to gold spraying and observed under SEM. The results are as follows: Figure 7 As shown, the borate bioactive glass synthesized by the traditional sol-gel method has irregular shapes, poor size controllability, and the particles are prone to agglomeration, making it difficult to use for nanoscale research and applications.
[0056] The above contents are only for explaining the technical idea of the present invention and cannot be used to limit the protection scope of the present invention. Any changes made on the basis of the technical solution in accordance with the technical idea proposed by the present invention shall fall within the protection scope of the claims of the present invention.
Claims
1. A method for preparing nano borate bioactive glass, characterized in that: include: At a certain temperature, a surfactant is added to an aqueous dispersion of ethyl acetate to form a microemulsion system, and the pH value is adjusted to alkaline to obtain an alkaline microemulsion system; Adding a boron source, a calcium source and a phosphorus source into an alkaline microemulsion system in sequence to react, thereby obtaining a precursor solution; After the precursor solution reacts and precipitates, the precipitate is collected, washed, dried, and then calcined to obtain the nano borate bioactive glass.
2. The method for preparing nano borate bioactive glass according to claim 1, characterized in that: The surfactant is a cationic surfactant; Preferably, the cationic surfactant includes at least one of dodecylamine, polyethylene glycol and dodecyltrimethylammonium.
3. The method for preparing nano borate bioactive glass according to claim 1, characterized in that: The volume ratio of ethyl acetate to water in the aqueous dispersion of ethyl acetate is 1:(1~4).
4. The method for preparing nano borate bioactive glass according to claim 1, characterized in that: Use alkali to adjust the pH value to 7.5~10.5; Preferably, an inorganic base or an organic base is used; More preferably, the inorganic base is aqueous ammonia, sodium hydroxide or potassium hydroxide; the organic base is triethanolamine, trimethylamine or triethylamine.
5. The method for preparing nano borate bioactive glass according to claim 1, characterized in that: The mass ratio of the boron source, phosphorus source, calcium source and surfactant is (20~90):(1~15):(10~65):(3~25).
6. The method for preparing nano borate bioactive glass according to claim 1, characterized in that: The boron source includes tributyl borate; the phosphorus source includes triethyl phosphate; and the calcium source includes calcium nitrate.
7. The method for preparing nano-borate bioactive glass according to claim 1, characterized in that: The certain temperature is 20~80℃; Preferably, the certain temperature is 30-60°C.
8. The method for preparing nano-borate bioactive glass according to claim 1, characterized in that: The calcination temperature is 400-800 °C, and the treatment time is 2-4 hours. The sintering system during the calcination process is: starting from room temperature, the temperature is increased at a heating rate of 3-15 °C / min. Preferably, the calcination temperature is 500-700° C., and the treatment time is 3 hours; the sintering system during the calcination process is: starting from room temperature, the temperature is increased at a heating rate of 5-10° C. / min.
9. The nano-borate bioactive glass prepared by the preparation method according to any one of claims 1 to 8, characterized in that: The chemical composition of the nano borate bioactive glass is aXO·bB2O3·cP2O5, wherein a, b and c are molar fractions, a is 3-50, b is 40-96, c is 1-10, and X is one or more of Ca, Mg and Sr.
10. The nano-borate bioactive glass according to claim 9, characterized in that: The nano borate bioactive glass is monodisperse, has a regular spherical shape, and has a particle size of 20 to 800 nm; Preferably, the particle size is 100-500 nm.
11. The nano borate bioactive glass according to claim 9, characterized in that: The chemical composition of the nano borosilicate bioactive glass includes one or more of the following: 3CaO·96B2O3·1P2O5; 12CaO·85B2O3·3P2O5; 25CaO·70B2O3·5P2O5; 30CaO·66B2O3·4P2O5; 42CaO·54B2O3·4P2O5; 54CaO·42B2O3·4P2O5.
12. Use of the nano borate bioactive glass according to any one of claims 9 to 11 in the preparation of biomedical materials.
Citation Information
Patent Citations
Micronano bioactive glass microsphere prepared by microemulsion technology and preparation method thereof
CN108083618A
Preparation method of micro-nano borosilicate bioactive glass
CN109336371A
Boron-doped bioactivity glass microspheres as well as preparation method and application thereof
CN110272209A
Injectable hydrogel with antibacterial and immunomodulatory activity as well as preparation method and application of injectable hydrogel
CN114796102A
Preparation method of zinc-doped radial mesoporous bioactive glass microspheres with immunoregulation function and product prepared by preparation method
CN117142767A